2015
DOI: 10.1016/j.wear.2015.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids as tribological performance improving additive for in-service and used fully-formulated diesel engine lubricants

Abstract: a b s t r a c tIn recent years, several papers have been published that investigate the potential use of ionic liquids (ILs) as additives in lubricants. However, corrosive attack of ILs on lubricated metal surfaces and low miscibility of ILs in the non-polar oils are major obstacles to maintaining an optimum lubrication performance level. High miscibility and no corrosive behaviour of Trihexyltetradecyl phosphonium bis(2,4,4-trimethylpentyl) phosphinate and Trihexyltetradecyl phosphonium bis(2-ethylhexyl) phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 30 publications
1
50
0
1
Order By: Relevance
“…In the latter case, the antagonistic interaction between IL2 and already-existing additives in New Oil could have led to the generation of stresses responsible for a higher film removal rate than the film formation rate [6]. The wear results for all the cases of Used Oil are in line with the ECR curves (Figure 3), such that they follow a same trend as the boundary film thickness.…”
Section: Wear Behaviorsupporting
confidence: 56%
See 3 more Smart Citations
“…In the latter case, the antagonistic interaction between IL2 and already-existing additives in New Oil could have led to the generation of stresses responsible for a higher film removal rate than the film formation rate [6]. The wear results for all the cases of Used Oil are in line with the ECR curves (Figure 3), such that they follow a same trend as the boundary film thickness.…”
Section: Wear Behaviorsupporting
confidence: 56%
“…In addition, the mixtures of Used Oil with both ILs outperformed the fully formulated New Oil (with/without ILs). These observations indicate either the synergistic interaction between the remaining content of already present additives in Used Oil and the later-added ILs (as demonstrated by the authors for high tempertaure testing in the past [6]) or the stronger affinity of ILs to form films on surfaces than the existing additives.…”
Section: Wear Behaviormentioning
confidence: 77%
See 2 more Smart Citations
“…Except for the polarity-induced surface absorption, under harsh sliding conditions, the active elements [N, F, P(B)] in ionic liquids offer sufficiently rich tribochemistry to form extreme pressure films of lower shearing strength by reacting with the fresh surface, which leads to lower friction coefficient and good wear resistance. It was found that ionic liquids as the additives in base oils also perform very well [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. The tribochemical reactions of ILs have been extensively studied.…”
Section: Ionic Liquids Additivesmentioning
confidence: 99%